Dedications as a source of important data: the case of Hamid Hadžibegić Library - Maslo, Amer; Ljuša, Lamija (Historical Thought, 2025)
During the war in Bosnia and Herzegovina 1992-1995, the special library of the Oriental Institute was destroyed. A significant contribution in the process of restoration and replenishment of the library fund in the post-war period was made by the Hamid Hadžibegić’s personal library, which arrived as a gift at the Oriental Institute in 2001. The library has over 1,000 publications that belonged to this established scientist and researcher of the past of Bosnia and Herzegovina, whose basic research had a strong influence in the scientific universe of Ottoman history researchers. This paper presents the dedications of colleagues and friends in his books and journals as cultural reminders and documentary records that, with their structure, text, dating and signature, represent a source of significant information about the life and work of this scientist.